Nicaragua betrayed by Anastasio Somoza - Cox, Jack (Estados Unidos | ESTADOS UNIDOS Western Islands, Boston, 1980)
Nicaragua Betrayed, published by Western Islands in 1980, is the memoir of former President of Nicaragua Anastasio Somoza Debayle (as told to Jack Cox), who had been toppled the previous year by the Sandinista insurgency. At the time of the book's publication, Somoza was living in Asunción, Paraguay, as a personal guest of President Alfredo Stroessner
Sin Especificar
Keywords: Nicaragua-Historia-1909-1979 | Guerra-Nicaragua